Effect of some abiotic factors on the population fluctuation of some pests infesting okra plants, with the using of some compounds in their controlling - Abdel Hamed, Neama A.; Shaalan, H. S.; Yasin, Samia A.; Abou-Zaid, Aziza M. M. (2011)
Field experiments were conducted at Qalyubiya Governorate during two successive seasons 2009 and 2010 to study the population fluctuation of some sapsucking pests, Bemisia labaci (Genn). Thrips labaci, Liriomyza lrifolii (Burgess) and Telranychus urlica Koch on Okra plants, and controlling them by using of Azadireohtin (NeemazaI5% EC), the natural oil (Clove oil, 5% EG), Plant extract Damaseia 1% DC and Vertimec 1.8% EG. Also the effect of these compounds and pests on chlorophyll of the leaves during the two successive seasons. The mean number of B. labacifirstly occurred on May 11'h and increased gradually to reach the peak at August 31" during 2009 season. While the infestation rates of T. labaci, L. lrifolii and T. urlica increased gradually and reached its peak in 14th , 3'd and 10th August in 2009 season, respectively. The weather factors (maximum, minimum, mean temperature) and plant age had significant positive effect on population of B. labaci, T. labaci, L. lrifolii and T. urlica while the relative humidity had negative significant effect on population of B. labaci, T. labaci, L. lrifolii and T. urlicae during the two studied seasons 2009 and 2010. The percentage of explained variance of the four tested factors during the two seasons were 91.50; 94.60% for B. labaci, 88.10; 89.90% in case of T. labaci, 73.40; 69.20% on L. lrifolii and 82.10 and 84.70 % for T. urlicae during the two seasons, respectively. The bioactivity of the four pesticides, the obtained results showed that Cloves oil, Damaseia and Neemazal seam to be closely similar in the order of mean reduction percentages of T. labaci, L. lrifolii and T. urlicae (59.53, 59.33&60.30), (54.00,55.90&55.10) and (76.20, 77.60&85.40, respectively) during the season 2009. On the other hand, Cloves oil caused 82.14 and 82.65 mortality of eggs and nymphal stages of whitefly followed by Damaseia (83.08&81.98) and Neemazal (75.50&73.30) during the two seasons. During 2009 season, the highest content of chlorophyll A in treated the okra leaves were obtained with using Cloves oil, VeI1imec and Plant Extract Damaseia in which the leaves had significantly more chlorophyll content than in control. During 2010 seasons, the leaves sprayed with Cloves oil had the highest amount of chlorophyll content, while plants sprayed with Vertimec showed significantly lower chlorophyll content than in the control plants.
Includes references.
Summary in Arabic.
1
Keywords: Okra -- Diseases and pests; Okra -- Diseases and pests -- Control; Greenhouse whitefly; Insect populations -- Estimates; population dynamics